Stick insects of Sulawesi, Peleng and the Sula Islands, Indonesia—a review including checklists of species and descriptions of new taxa(Insecta: Phasmatodea) - Hennemann, Frank H. (Zootaxa, 2021)
A review of the stick and leaf insects of Sulawesi, Peleng Island and the Sula islands is presented, along with complete checklists of species. The genera Hemiplasta Redtenbacher, 1908 and Nesiophasma Günther, 1934 are reviewed in detail and distinguishing keys to all known species are provided. Distinguishing keys are also provided to the Sulawesian species of Dimorphodes Westwood, 1859 and Nescicroa Karny, 1923. The latter genus is removed from synonymy with Paranecroscia Redtenbacher, 1908 and re-established as a valid genus (rev. stat.), with a new diagnosis and a preliminary list of species provided. As a result, 17 species are here transferred back to Nescicroa (rev. comb.). The genus Cylindomena Günther, 1935 is removed from synonymy with Parasipyloidea Redtenbacher, 1908 and re-established as a valid genus (rev. stat.). Consequently, the two species originally attributed to Cylindomena are re-transferred to the genus (rev. comb.). A new diagnosis along with a list of species is also given for the genus Myronides Stål, 1875, which is shown to be geographically restricted to Wallacea. Three new genera in Lonchodidae: Lonchodinae are described from Sulawesi. Gibbopromachus n. gen. is established only for the type-species Pericentrus tripinnatus Redtenbacher, 1908, a species restricted to mossy, mountainous habitats in North Sulawesi; consequently this species now becomes Gibbopromachus tripinnatus (Redtenbacher, 1908) n. comb.. The new genus Neomyronides n. gen. (Type-species: Pseudostheneboea aberrans emiri Hennemann, 1998) is established to comprise three species that have previously been misplaced in other genera. Paramanduria n. gen. is erected to comprise its type-species Neopromachus celebensis Günther, 1935 as well as Prisomera nodosum Günther, 1938; hence these two species change to Paramanduria celebensis (Günther, 1935) n. comb. and Paramanduria nodosum (Günther, 1938) n. comb.. Twenty-two new species are described, 14 from Sulawesi, one from the Togian islands, five from the island of Peleng and two from the island of Sanana. Sulawesi: Dimorphodes elegans n. sp. is decribed from the male and female, Hemiplasta flavifrons n. sp. from the male, Hemiplasta parva n. sp. from the male, Leprocaulinus digitatus n. sp. from the female, Leprocaulinus sulawesiense n. sp. from the male, female and egg, Mnesilochus bodiense n. sp. from the male, Mnesilochus luwuense n. sp. from the female, Myronides tomohonense n. sp. from the male and female, Necroscia malleoformia n. sp. from the male, Nescicroa splendida n. sp. from the male and female, Periphetes borealis n. sp. from the male, Ramulus extensus n. sp. from the male, Ramulus melanurus n. sp. from the male and Ramulus torajanus n. sp. from the male, female and egg. Togian Islands: Ramulus togianense n. sp. is described from both sexes and the eggs. Peleng: Myronides glaucus n. sp., Nesiophasma giganteum n. sp. and Ramulus pelengense n. sp. are described from both sexes and the eggs, Orthomeria limogesi n. sp. from the male and female and Pylaemenes pleurospinosus n. sp. from the female only. Sanana Island: Myronides pussulatus n. sp. and Nesiophasma sananaense n. sp. are described only from the female sex. Ten species are synonymised (n. syn.): Calvisia (Conocalvisia) octolineata Redtenbacher, 1908 and Calvisia (Conocalvisia) reductipennis Redtenbacher, 1908 synonymised with Calvisia (Conocalvisia) hippolyte (Westwood, 1859); Lonchodes reductus Brunner v. Wattenwyl, 1907 synonymised with Myronides cristulatus Brunner v. Wattenwyl, 1907; Necroscia albofasciata Redtenbacher, 1908 synonymised with Nescicroa smaragdula (Bates, 1865); Necroscia densegranulosa Redtenbacher, 1908 and Sipyloidea (Hemiplasta) falcata Redtenbacher, 1908 synonymised with Hemiplasta mustea (Bates, 1865) n. comb.; Paranecroscia frontalis (Redtenbacher, 1908) synonymised with Nescicroa viridilineata (Bates, 1865); Paranecroscia graminea (Bates, 1865: 356), here synonymised with Nescicroa smaragdula (Bates, 1865); Ramulus melanocephalus (Carl, 1913) synonymised with Ramulus supernumerarius (Brunner v. Wattenwyl, 1907); Sipyloidea felderi Redtenbacher, 1908 synonymised with Singaporoidea poeciloptera (Rehn, 1904) n. comb.. Six subspecies are raised (n. stat.) or re-transferred (rev. stat.) to species level: Dimorphodes celebensis Redtenbacher, 1908 rev. stat., Dimorphodes sarasini Redtenbacher, 1908 rev. stat., Hermagoras celebensis (Hennemann, 1998) n. stat., Leprocaulinus mammatus (Rehn, 1904) rev. stat., n. comb., Neomyronides emiri (Hennemann, 1998) n. comb., n. stat., Nescicroa rufescens (Hennemann, 1998) n. stat.. Hemiplasta rostrata (Redtenbacher, 1908) is removed from synonymy with Hemiplasta styligera (Bates, 1865) and Sipyloidea normalis Redtenbacher, 1908) is removed from synonymy with Sipyloidea poeciloptera Rehn, 1904; both are re-established as a valid species (rev. stat.). 37 species are transferred to other genera (n. comb.): Asceles morio (Redtenbacher, 1908), Asceles roseonotata (Redtenbacher, 1908), Dimorphodes epidicus (Günther, 1935), Gibbopromachus tripinnatus (Redtenbacher, 1908), Hemiplasta mustea (Bates, 1865), Hemiplasta nigra (Hennemann, 1998), Leprocaulinus heinrichi (Günther, 1935), Leprocaulinus kaupii (Stål, 1875), Leprocaulinus mammatus (Rehn, 1904), Lopaphus ashmeadi (Rehn, 1904), Lopaphus baucis (Westwood, 1859), Lopaphus elegans (Brunner v. Wattenwyl, 1907), Lopaphus magnificus (Brunner v. Wattenwyl, 1907), Myronides batesii (Kirby, 1896), Neomyronides aberrans (Günther, 1938), Neomyronides emiri (Hennemann, 1998), Neomyronides obsolefactum (Günther, 1935), Nescicroa ruficeps (Redtenbacher, 1908), Ophicrania bojei (Haan, 1842), Paramanduria celebensis (Günther, 1935), Paramanduria nodosum (Günther, 1938), Phraortes curvithorax (Brunner v. Wattenwyl, 1907), Ramulus supernumerarius (Brunner v. Wattenwyl, 1907), Rhamphosipyloidea tristis (Redtenbacher, 1908), Singaporoidea albilateralis (Hennemann, 1998), Singaporoidea dolorosa (Redtenbacher, 1908), Singaporoidea fruhstorferi (Günther, 1938), Singaporoidea inconspicua (Redtenbacher, 1908), Singaporoidea janus (Bates, 1865), Singaporoidea lutea (Redtenbacher, 1908), Singaporoidea macra (Redtenbacher, 1908), Singaporoidea normalis (Redtenbacher, 1908), Singaporoidea poeciloptera (Rehn, 1904), Singaporoidea pseudosipylus laevis (Günther, 1936), Singaporoidea pseudosipylus pseudosipylus (Redtenbacher, 1908), Singaporoidea pumila (Werner, 1934) and Singaporoidea tenella (Günther, 1935). 20 species are transferred back to the genera they have been placed in previously (rev. comb.): Cylindomena acuminata (Redtenbacher, 1908), Cylindomena scalprifera Günther, 1935, Nescicroa angustata (Redtenbacher, 1908), Nescicroa compacta (Redtenbacher, 1908), Nescicroa contracta (Redtenbacher, 1908), Nescicroa heinrichi (Günther, 1935), Nescicroa obliterata (Redtenbacher, 1908), Nescicroa papuana (Brancsik, 1898), Nescicroa rammei (Günther, 1935), Nescicroa redempta (Redtenbacher, 1908), Nescicroa resignata (Redtenbacher, 1908), Nescicroa rivalis (Redtenbacher, 1908), Nescicroa rufescens (Hennemann, 1998), Nescicroa sanguinata (Redtenbacher, 1908), Nescicroa smaragdula (Bates, 1865), Nescicroa tereticollis (Redtenbacher, 1908), Nescicroa terminalis (Redtenbacher, 1908), Nescicroa tumescens (Redtenbacher, 1908) and Nescicroa viridilineata (Bates, 1865). The world‘s longest stick insect Phobaeticus chani Bragg, 2008 is removed from the genus Sadyattes Stål, 1877 (Platycraninae: Stephanacridini) and transferred back to its original genus Phobaeticus Brunner v. Wattenwyl, 1907 (Clitumninae: Clitumnini) rev. comb.. Lectotypes are designated for 17 species: Aruanoidea inconspicua Redtenbacher, 1908; Calvisia octo-lineata Redtenbacher, 1908; Calvisia reductipennis Redtenbacher, 1908; Clitumnus redemptus Brunner v. Wattenwyl, 1907; Cuniculina melanocephala Carl, 1913; Datames moluccanus Redtenbacher, 1906; Dimorphodes bellicosus Redtenbacher, 1908; Dimorphodes celebensis Redtenbacher, 1908; Myronides cristulatus Brunner v. Wattenwyl, 1907; Necroscia frontalis Redtenbacher, 1908; Necroscia viridilineata Bates, 1865; Phobaeticus kuehni Brunner v. Wattenwyl, 1907; Phryganistria plateni Dohrn, 1910; Sipyloidea felderi Redtenbacher, 1908; Sipyloidea normalis Redtenbacher, 1908; Sipyloidea (Hemiplasta) falcata Redtenbacher, 1908; and Sipyloidea (Hemiplasta) rostrata Redtenbacher, 1908. The male of Hemiplasta styligera (Bates, 1865) and Paracyphocrania major Hennemann, Conle & Suzuki, 2015 are described and illustrated for the first time and information on the natural habitats, host plants and life-cycle of the latter species in Peleng are provided. The egg of Dimorphodes sarasini Redtenbacher, 1908 is described and illustrated for the first time.